Introducing Marketing 4.0 in Gen Z Through Project-Based Learning - Falahah; Munandar, Fajar (Journal of Informatics and Communication Technology (JICT), 2025)
Marketing 4.0, as the newest marketing paradigm, has become an important skill for everyone involved in sales and marketing. As a dominant part of the recent generation, Gen Z become a main component of Marketing 4.0 as they can be an actor or a person affected. The initiative for learning Marketing 4.0 in Gen Z is generally done at higher level education (university), MSME actors, or vocational high school students. However, introducing it in high school, in general, is still very rare. The research aims to explore how to introduce Marketing 4.0 to general high school students through project-based learning (PBL) and to know the effectiveness of this method in understanding Marketing 4.0 among students. The project is implemented for 10-th grade students of SMA Negeri 5 Bandung, executed through two cycles, and integrated with program P5 (Projek Penguatan Profil Pelajar Pancasila), which chooses Marketing 4.0 as a specific theme. The observation results show that there has been a significant increase in students' understanding and implementation of the Marketing 4.0 approach in marketing and selling products. The questionnaire results also show that the PBL approach is considered effective in increasing students' knowledge of Marketing 4.0, and this project has succeeded in providing valuable and useful experience for students